2021
DOI: 10.3390/jmse9080822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modified Clay on the Growth Dynamics and Physio—Biochemical Response of Newly Hatched Larvae of the Marine Medaka (Oryzias melastigma)

Abstract: An outbreak of harmful algal blooms (HABs) often leads to the death of fish and other marine organisms and causes serious losses to human economic activities. Modified clay (MC) technology is an effective way to control HABs. Although the material and preparation process are based on the premise of green and safety, the potential eco-environmental impacts of MC on non-target organisms should still have to receive attention before field applications can occur. Therefore, the effects of one commonly used modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The SOD–CAT system is known as a first line of defense against oxidative stress [25] . The present study also showed that pH affects the activity of two key enzymes (CAT and SOD) in M. chinensis juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…The SOD–CAT system is known as a first line of defense against oxidative stress [25] . The present study also showed that pH affects the activity of two key enzymes (CAT and SOD) in M. chinensis juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…Predecessors have performed much research on the safety of MC. The appropriate concentration of MC had no significant effect on the survival and growth of Crassostrea gigas juveniles, Apostichopus japonicas Selenka juveniles, Patinopecten yessoensis juveniles, Mercenaria mercenaria , Haliotis discus hannai , Scophthalmus maximus embryos, O. melastigma newly hatched larvae, etc [ 7 , 28 , 33 , 40 , 43 , 44 , 45 ]. The results of this study showed that 0.3 g/L MC did not have a significant impact on the survival of marine medaka.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of MC used in this experiment should meet the requirement of high removal rate of K. mikimotoi and no significant effect on the survival of marine medaka. 0.3 g/L of MC can remove 80% of K. mikimotoi cells in the water column, and it is lower than the safe concentration (1.94 g/L) of MC for newly hatched larvae of marine medaka [ 40 ]. Therefore, 0.3 g/L was chosen as the concentration of MC used in the experiment.…”
Section: Methodsmentioning
confidence: 99%